Fields, Power and Social Skill: a Critical Analysis of the New Institutionalisms - Нил Флигстин (Journal of Economic Sociology, 2010)
“The new institutional” theories are widely spread in social sciences. Despite the considerable contradictions in these theories, they all claim that social institutions give rise to local social orders and that they are social constructions.  They tell us how the power groups set up the interaction rules and provide the situation of unequal resource distribution. While appearing the institutions limit the actors’ actions and at the same time encourage the further institutional construction. This paper criticizes these theories focusing on the lack of attention to the role of social authorities and actors in the process of the institutions’ creation. The author gives an alternative approach to the institutional dynamics, based on sociological understanding of the rules, resources and social skill.